The Effectiveness of Hajj Pilgrim Registration Services in the Satu Haji Application at the Ministry of Religious Affairs Office of Mukomuko Regency - Refazzatul Ummamah; Khairiah Elwardah; Makmur Makmur (Asosiasi Dosen Muda Indonesia, 2026)
The Satu Haji application is a platform developed to facilitate the registration process for Hajj pilgrims. However, several challenges have been encountered in its implementation. Some pilgrims experience difficulties in using the application due to limited technological literacy. This study aims to evaluate the feasibility of the Satu Haji application in supporting Hajj registration services at the Ministry of Religious Affairs Office of Mukomuko Regency. Additionally, it seeks to analyze the supporting and inhibiting factors affecting the effectiveness of the application in the registration service process. This study employs a descriptive qualitative method, with data collected through field interviews and observations. The results indicate that the Satu Haji application has made a significant contribution to improving the effectiveness of Hajj registration services. Through this application, pilgrims are able to register online easily and efficiently without the need to visit the office in person. Furthermore, the application provides comprehensive information regarding requirements, schedules, and registration procedures.